Deposit insurance and moral hazard: does the counterfactual matter? - Reint E. Gropp; Jukka Vesala (European Central Bank (ECB), 2001)
The paper analyses the relationship between deposit insurance, debt-holder monitoring, charter values and risk taking. Utilising cross-sectional and time series variation in the existence of deposit insurance schemes in the EU, we find that the establishment of explicit deposit insurance significantly reduces the risk taking of banks. This finding stands in contrast to most of the previous empirical literature. It supports the hypothesis that in the absence of deposit insurance, European banking systems have been characterised by strong implicit insurance operating through the expectation of public intervention at times of distress. We also test further hypotheses regarding the interaction between deposit insurance and monitoring, charter values and 'too-big-to-fail.' We find that smaller banks and banks with lower charter values and more subordinated debt reduce risk taking more after the introduction of explicit deposit insurance, which supports 'too-big-to-fail', monitoring by debt holders and the moral hazard reducing effect of charter values.
Keywords: G21; G28; 330; banking; Charter Value; Deposit Insurance; Safety Net; Subordinated debt